The dawn of a dynasty: life strategies of Cambrian and Ordovician brachiopods. (6th July 2017) - Topper, Timothy P.; Zhang, Zhifei; Gutiérrez‐Marco, Juan Carlos; Harper, David A. T.
Abstract : Brachiopods are among the first animal phyla to emerge from the Cambrian Explosion, rapidly diversifying to all major palaeocontinental blocks within 20 million years. The group underwent another steep rise in diversity during the Ordovician, and their relative abundance and diversity made them one of the most successful invertebrate groups during the entire Palaeozoic. During this time, brachiopods lived in a range of environments and represented a significant component of marine ecosystems, yet information regarding their modes of life and ecology is somewhat limited. Recent studies, primarily from the Chengjiang and Burgess Shale Lagerstätten, have revealed that by the Middle Cambrian (Series 3, Stage 5) brachiopods from across the phylum had already developed a range of ecological strategies and life modes. Cambrian brachiopods occupied distinct trophic niches on soft and hard substrates and exhibited at least five types of lifestyles: pedicle attachment, pedicle anchoring, cemented, free‐lying and semi‐infaunal. Comparisons with Ordovician benthic assemblages show that despite the explosion of brachiopod taxa witnessed in the Ordovician, with the exception of the appearance of burrowing brachiopods, life strategies of brachiopods remained largely the same. Indicating that the majority of life modes observed in brachiopods had rapidly evolved and was already in place prior to the Great Ordovician Biodiversity Event.